"Pathologic foresight" syndrome and its place in the onset of paranoid schizophrenia - S. V. Litvintsev (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The psychopathologic structure of „pathologic foresight“ syndrome and its place in the onset of paranoid schizophrenia are considered in the article. It is noted that contemporary mass media largely influence its forming. It is supposed that the syndrome is a kind of paranoiac syndrome following from picturesque delusion. The necessity of the timely detection of „pathologic foresight“ syndrome for the early diagnostics and prognostic assessment of paranoid schizophrenia stochastic course is stressed. It is important for the effective organization of medical and rehabilitation measures with the disease beginning.